2004
DOI: 10.1016/j.femsyr.2004.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Different action of killer toxins K1 and K2 on the plasma membrane and the cell wall of

Abstract: Study of Saccharomyces cerevisiae killer toxin-sensitive strains with the deltakre2 phenotype (resistant to toxin K1, sensitive to toxin K2) showed that the phenotype is complemented by the KRE2 gene not only in intact cells but also in spheroplasts, and resistance to K1 thus resides very probably in the plasma membrane. deltakre1 deletant displays a faulty interaction with both K1 and K2 toxin. Hence, Kre1p probably serves as plasma membrane receptor for both toxins. Deletants in seven other genes (GDA1, SAC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Similar observations were made previously for several kre mutants with increased resistance to K2 toxin and therefore decreased survival (20), but this phenomenon was not correlated with changes in ␤-1,6-glucan level. Still, we cannot exclude the possibility that in addition to the altered level of this glucan in the tested mutants, the survival of cells may be modulated by other cellular processes due to changed cellular levels of the tested proteins.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar observations were made previously for several kre mutants with increased resistance to K2 toxin and therefore decreased survival (20), but this phenomenon was not correlated with changes in ␤-1,6-glucan level. Still, we cannot exclude the possibility that in addition to the altered level of this glucan in the tested mutants, the survival of cells may be modulated by other cellular processes due to changed cellular levels of the tested proteins.…”
Section: Discussionsupporting
confidence: 87%
“…Analysis of the sensitivity of a ⌬kre1 mutant to either K1 or K2 toxin demonstrated total resistance in both cases, suggesting that Kre1p serves as plasma membrane receptor (19,20). Also, it was shown that both K1 and K2 bind less efficiently to a set of mutants featuring a decreased level of ␤-1,6-glucan, implying that it serves as a cell wall receptor for both proteins (9,19,20). Despite the similarities between the K1 and K2 toxins and taking into account the abovementioned differences among them, the details of killer protein interactions with the target cells and immunity mechanisms remain to be uncovered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are two kinds of killer toxin receptors: the primary, usually located on the cell wall, and the secondary receptor, that exist on the plasma membrane of the sensitive cells. The interaction with the first receptor within the cell wall of a sensitive target cell involves a fast and energy-independent binding [20,49,75,76,95,96,97,98,99]. Cell walls are mainly composed by carbohydrates, some of them free and some linked to proteins.…”
Section: Killing Mechanism Of Actionmentioning
confidence: 99%
“…Mutational analyses reveal that solely α subunit interacts with Kre1p. Δ KRE1 mutants show complete resistance to K1, indicating that Kre1p acts as a receptor in the cytoplasmic membrane [21,98,99,103,112]. …”
Section: Killing Mechanism Of Actionmentioning
confidence: 99%